The Management and Coordination of Virtual Teams in Large Classes: Facilitating Experiential Learning. (October 2021) - O'Connor, Christina; Mullane, Kenneth; Luethge, Denise
The management and coordination of classroom teaching continues to be a challenge, particularly as enrollment trends suggest that class sizes are growing. In the past, many faculty have divided their large classes into smaller groups to incorporate experiential exercises. In this article, we discuss the challenges of managing an experiential exercise featuring a large number of teams in a virtual setting. These challenges include (a) coordinating class communication with a large number of teams, (b) managing teams and facilitating team communication and trust, (c) managing virtual team performance and instructor feedback throughout the experiential exercise, and (d) managing and evaluating student engagement. We also provide practical suggestions for management educators on how to address each challenge based on insight gleaned from our years of experience using virtual teams in large classes. Finally, we highlight avenues for future research in the area of virtual teams and large class size teaching.